Nestin and cluster of differentiation 146 expression in breast cancer: Predicting early recurrence by targeting metastasis?. Issue 3 (February 2017) - Tampaki, Ekaterini Christina; Tampakis, Athanasios; Nonni, Afroditi; Kontzoglou, Konstantinos; Patsouris, Efstratios; Kouraklis, Gregory
The purpose of this study was to investigate the relationship between the expression of stem-cell markers nestin and cluster of differentiation 146 with clinicopathological characteristics in breast cancer and to determine whether a prognostic impact of nestin and CD146 expression exists regarding occurrence of disease relapse in breast cancer. A total of 141 patients who were histologically diagnosed with breast cancer and underwent radical operations from November 2006 to October 2013 in Laiko General Hospital, National and Kapodistrian University of Athens, were enrolled in the study. CD146 and nestin protein expression were evaluated using immunohistochemistry. Nestin expression was observed in 18.4% (26/141) of the cases, while CD146 expression was observed in 35.5% (50/141) of the cases. Nestin expression is significantly higher in younger patients with breast cancer. Nestin and CD146 expression were not correlated with the tumor size and the presence of lymph node metastasis. On the contrary, a significantly higher expression of nestin and CD146 was observed with triple-negative cancers (p < 0.0001 for both markers), low differentiated tumors (p = 0.021 for nestin and p = 0.008 for CD146), and increased Ki-67 expression (p = 0.007 for nestin and p < 0.0001 for CD146). The nestin-positive group of patients and the CD146–positive group of patients presented significantly higher rates of disease recurrence (log-rank test, p = 0.022 for nestin and p = 0.003 for CD146) with a distant metastasis, 30 months after the primary treatment. CD146 but not nestin, however, predicted independently (p = 0.047) disease recurrence. Nestin and CD146 are expressed in breast cancer cells with highly aggressive potency. They might contribute to disease relapse in breast cancer by activating the epithelial–mesenchymal transition pathway and assist tumor neovascularization.